2012
DOI: 10.1038/tp.2012.41
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analyses of smoking behaviors in African Americans

Abstract: The identification and exploration of genetic loci that influence smoking behaviors have been conducted primarily in populations of the European ancestry. Here we report results of the first genome-wide association study meta-analysis of smoking behavior in African Americans in the Study of Tobacco in Minority Populations Genetics Consortium (n=32 389). We identified one non-coding single-nucleotide polymorphism (SNP; rs2036527[A]) on chromosome 15q25.1 associated with smoking quantity (cigarettes per day), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
3
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 59 publications
2
107
3
1
Order By: Relevance
“…As previously observed (The Tobacco and Genetics Consortium, 2010), CHRNA3-CHRNA5 rs8034191, rs1051730, and rs16969968 were strongly associated with smoking quantity (ie, cigarettes per day) in European subjects. We also replicated the association of CHRNA5 rs2036527 with the same trait in the AFR sample, consistent with results from a large GWAS of smoking quantity in African-American subjects (David et al, 2012). Unfortunately, we were not able to replicate the associations of CHRNA5 rs12914385, likely because the genotypes for this variant were not available for the PAGE WHI cohort and therefore the data were available in only 36% of the total sample (2% of the total EUR sample).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As previously observed (The Tobacco and Genetics Consortium, 2010), CHRNA3-CHRNA5 rs8034191, rs1051730, and rs16969968 were strongly associated with smoking quantity (ie, cigarettes per day) in European subjects. We also replicated the association of CHRNA5 rs2036527 with the same trait in the AFR sample, consistent with results from a large GWAS of smoking quantity in African-American subjects (David et al, 2012). Unfortunately, we were not able to replicate the associations of CHRNA5 rs12914385, likely because the genotypes for this variant were not available for the PAGE WHI cohort and therefore the data were available in only 36% of the total sample (2% of the total EUR sample).…”
Section: Discussionsupporting
confidence: 61%
“…We chose these variants on the basis of numerous GWAS (Gelernter et al, 2014;Xu et al, 2015) and candidate-locus studies (Sherva et al, 2010;Hart et al, 2015;Jensen et al, 2015), and a recent meta-analysis of genetic studies of nicotine and alcohol traits (Buhler et al, 2015) and GWAS performed previously in different population groups (David et al, 2012;Gelernter et al, 2014).…”
Section: Genotype Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported a genetic predisposition (8)(9)(10)(11) to cigarette smoking. Other studies have reported smokingrelated DNA methylation patterns (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) and meta-analyses of GWAS have identified single nucleotide polymorphisms (SNPs) that are associated with alcohol dependence and smoking phenotypes [7][8][9]. In a review of these and candidate gene studies, Bühler et al [10•] reported that the most robust associations involve SNPs in the alcohol metabolizing genes, the cholinergic gene cluster, and in the dopamine D2 receptor (DRD2) and Ankyrin repeat and kinase domain containing 1 (ANNK1) genes.…”
Section: Introductionmentioning
confidence: 99%